The Soft Side of Knowledge Management in Health Institutions - Johannessen, Jon-Arild (Emerald points., 2021)
The Soft Side of Knowledge Management in Health Institutionsexamines how a knowledge perspective and knowledge-effectiveness can contribute to improving hospital leadership and organisation from a continuous-change perspective.